Amphiphilic ligand in situ assembly of uranyl active sites and selective interactions of molybdenum disulfide - Liu, Yuhui (2023)
Removal of radioactive uranyl ions (UO22+) from water by effective adsorbents is highly desired but remains a challenge. UO22+ are easily combined with H2O, and the polarization of H2O affects the complexation between UO22+ and the adsorbent. Thus, it is necessary to reconstruct the UO22+ active site to improve the adsorption capacity. Herein ，an amphiphilic ligand, namely N, N-dimethyl-9-decenamide (NND), is successfully prepared. NND replace H2O in [UO2(H2O)5]2+ by hydrogen bonding, thereby enhancing the adsorption capacity of MoS2 particles in the reconstituted UO22+ active sites. The predicted maximum adsorption capacity increased from 50.7 to 500.7 mg g- 1 (by a factor of 9.87) with the presence of NND, which is higher than other functional group-modified MoS2 adsorbents. Furthermore, NND and MoS2 can retain UO22+ uptake under extreme conditions including high acid-base and gamma irradiation. Theoretical Calculations of NND through H bonding produces an increased amount of charge transfer and a reduced adsorption energy between UO22+ and MoS2, which weakens the polarization effect of H2O. The findings showed that NND appeared to be a promising amphiphilic to improve the adsorption efficiency of UO22+ from water.